Demographics, Clinical Profile, Cause and Outcome of Epilepsy in Neurosurgical Unit in Manipal Teaching Hospital in Western Nepal - Adhikari, Suman; Bhandari, Prabin; Karmacharya, Balgopal; Yogi, Nikunja (Eastern Green Neurosurgery, 2020)
Background: Epilepsy is a common chronic disorder characterized by recurrent unprovoked seizures. Around 50 million people worldwide have epilepsy and almost 80% of people with epilepsy live in low and middle-income countries. Most of these people do not get the necessary treatment they need. The main objective of this study is to study the demographic profile of patients, etiology of epilepsy and prescribing pattern, drug compliance, and its outcome in terms of epilepsy control in patients. Materials and methods: A retrospective analytical study was conducted from January 2018 to December 2018 including 120 consecutive patients admitted with epilepsy with an objective to study various clinico-socio-demographical features of epilepsy and various features associated with outcome. The outcome was categorized into a good outcome group and poor outcome group according to absence or decrease in seizure frequency in 6 months duration in comparison to the pre-treatment status. All the continuous variables were compared in relation to the outcome using the student’s t-test and the categorical data were compared using Chi-square and Fischer Exact test. Data analysis was done using SPSS 20.0 software. Results: The mean age of the study population was 37.8 ± 21.1 years (4 months -95 years). Mean hospital stay was 11.97 ± 11.5 days. There were 79 (65.83%) males and 41 (34.17% females in the study. Ninety seven (80.83%) of the patients in our were educated above high school level and literacy level showed statistically significant association with good seizure control (p=0.043). One hundred thirteen patients had Generalized Tonic-Clonic Seizures and 7 patients had a partial seizure. Levetiracetam (52, 43.3%) was the commonest antiepileptic used in our series, and polytherapy was used in 15 (12.5%) of patients. Intracerebral hemorrhage (39.2%) and Trauma (36.7%) were the commonest cause of epilepsy in our series. Conclusion: Drug compliance played a pivotal role in determining good seizure control vs. poor seizure control. Additionally, the literacy level of the patient determined drug compliance and thus seizure control.